Antecedents of E-Loyalty: The Mediating Role of E-Trust among Nepalese E-Commerce Consumers - Chaudhary, Manoj Kumar; Ghimire, Dinesh Mani; Adhikari, Madhav; Poudel, Dibyanshu (Nepal Journal of Multidisciplinary Research, 2025)
Purpose: This paper examines the antecedents of e-commerce loyalty (ECL) in the Nepalese market, with the mediating role of e-commerce trust (ECT). It explores how factors such as perceived security risk, perceived privacy, user interface quality, information quality, and e-commerce awareness influence trust and subsequently drive loyalty. Design/Methodology/Approach: A quantitative method was utilized, employing structured Likert-scale questionnaire to collect data from 425 respondents in Kathmandu, Lalitpur, and Bhaktapur. Hayes Process Macro Model 4 were employed to analyze and direct and mediated relationships among variables. Findings: The findings reveal that ECT significantly mediates the impact of information quality, and perceived privacy on ECL, with trust amplifying their effects emphasizing its pivotal role in alleviating consumer concern. E-commerce awareness emerged as direct predictors of loyalty. Perceived privacy and perceived security risk have significant influence loyalty indirectly through trust. Implication: Insights from this research are invaluable for e-commerce businesses and policymakers aiming to cultivate trust and loyalty in developing markets like Nepal. Strategies focusing on consumer-centric design and communication of privacy and security policies can enhance loyalty and sustainable growth. Originality: This research adds to the limited number of scholarly papers on e-commerce loyalty in Nepal, providing a comprehensive framework for understanding the mediating influence of trust in the e-commerce ecosystem.